TREATMENT OF EPILEPSY IN TUBEROUS SCLEROSIS - E. D. Belousova; M. Y. Dorofeeva; T. G. Ohapkina (Эпилепсия и пароксизмальные состояния, 2016)
Epilepsy is the most frequent neurological sign of tuberous sclerosis complex (TSC) and it’s registered in 83.5% of patients. In majority of cases epilepsy begins during the first year of life (63%) and in 38.8% it’s manifesting as infantile spasms. The presence of epilepsy is closely connected with development of mental retardation in TSC. Early treatment of epilepsy is a key to prevention of mental retardation, and preventive treatment with vigabatrin is now advised by some specialists. Possibly high efficasy of vigabatrin in treatment of seizures associated with TSC is partly due to its m-TOR inhibiting property. M-TOR way is widely discussed now as one of the perspective targets for epilepsy treatment, associated or not associated with TSC.